Method for preparing methanol based on carbon dioxide capture, method for preparing ethylene glycol and environmentally friendly polyester

By adopting a porous structure catalyst and multi-stage fixed bed reactor design, the conversion rate and selectivity of carbon dioxide and hydrogen reaction are improved, and the problem of low catalyst efficiency in the prior art is solved. At the same time, ethylene glycol is prepared through MTO technology and appropriate catalysts and stabilizers are used in the polyester synthesis process to achieve the preparation of green and environmentally friendly ethylene glycol and the production of high-performance polyester.

CN119118791BActive Publication Date: 2025-04-22JIANGSU ZHONGLU TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411263162.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-22
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing catalysts for reacting carbon dioxide with hydrogen to prepare methanol have problems with low conversion and poor selectivity. When methanol is further used to synthesize ethylene glycol, there are many types of impurities in ethylene glycol, which makes it difficult to directly be used for the synthesis of polyester.

Method used

The copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst and copper-zirconium-titanium-vana-vana deposition hydrogenation catalyst are designed through a multi-stage fixed-bed hydrogenation reactor to improve the conversion rate and reaction selectivity of carbon dioxide. At the same time, ethylene glycol is prepared through MTO technology, and an esterification catalyst and composite stabilizer are used in the preparation of ethylene glycol and polyester synthesis process to ensure the performance of the polyester.

Benefits of technology

The conversion rate and reaction selectivity of carbon dioxide are significantly improved, the preparation of green and environmentally friendly ethylene glycols produced in low-carbon production is realized, and the performance of polyester is basically at the level of petrochemical methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118791B_ABST
    Figure CN119118791B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing methanol based on carbon dioxide capture, a method for preparing ethylene glycol and an environmentally friendly polyester. The method captures and purifies a high-concentration carbon dioxide gas stream produced as a byproduct of a petroleum refining process into high-purity carbon dioxide, and then sequentially performs hydrogenation reactions in a three-stage fixed bed reactor to prepare green methanol, wherein a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is used in the first-stage and third-stage reactors, and a copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst is used in the second-stage reactor. The green methanol can be used to prepare green ethylene glycol through an MTO process, ethylene oxidation, and ethylene oxide hydrolysis. The green ethylene glycol and terephthalic acid (PTA) can be used to prepare an environmentally friendly carbon-reducing polyester through slurry preparation, esterification reaction, and polymerization reaction; during the esterification and polymerization process, by adding a specific esterification catalyst and a composite stabilizer, the performance of the environmentally friendly carbon-reducing polyester can be improved, making it comparable to the performance of the polyester product corresponding to the petrochemical method ethylene glycol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of petrochemical industry and polyester chemical technology, and specifically relates to a method for preparing methanol based on carbon dioxide capture, and a method for preparing ethylene glycol and environmentally friendly polyester. Background Art

[0002] In recent years, fossil fuels such as oil, coal, and natural gas have gradually been depleted both at home and abroad, resulting in excessive greenhouse gas emissions entering the atmosphere. The original self-carbon cycle environment of the earth has been destroyed with the increasing greenhouse gases; large amounts of carbon dioxide emissions are the direct cause of global warming and the extreme weather that has occurred in recent years.

[0003] Entering the 21st century, the call for green, sustainable, biodegradable, carbon-reducing and environmentally friendly development has been growing louder. With the development of new technologies around the world, it has gradually been implemented in many specific development areas, including the use of solar energy driven by the photovoltaic industry, wind power generation technology driven by lightweight and high-strength materials such as carbon fiber, large-capacity hydropower generation and tidal power generation technology under development, and other new energy technologies. These have provided a new energy field and greatly reduced the consumption of fossil energy. The proportion of these green energies has further increased, providing a clear development direction for the world to achieve a low-carbon economy.

[0004] In this environment, carbon capture technology has developed accordingly. This technology can reduce emissions of carbon dioxide greenhouse gases by means of storage and chemical conversion. The use of carbon dioxide storage is only a short-term control of greenhouse gas emissions, and cannot fundamentally solve the problem of carbon dioxide emissions. The development of large-capacity carbon dioxide capture and purification PSA device technology can simply increase the content of carbon dioxide and purify the quality of carbon dioxide. The research on chemical conversion technology of carbon dioxide supported by green energy has now rapidly developed from laboratory research and development to pilot-scale expansion and industrialization technology. Using carbon dioxide as a raw material and reacting with hydrogen to synthesize methanol can, on the one hand, capture CO2 in industrial waste gas, and can improve the high-concentration carbon dioxide gas flow from large-scale thermal power and refining tail gas emitted in a centralized manner to a high purity level through simple purification technology, meeting the quality requirements of carbon dioxide hydrogenation to produce methanol. On the other hand, various green energy sources can be used to produce hydrogen by electrolysis, providing completely green hydrogen resources. Carbon dioxide hydrogenation to methanol technology can provide a new and convenient idea for methanol production and energy storage, and has important promotion value.

[0005] The core of the technology for preparing methanol from carbon dioxide and hydrogen is the selection and synthesis of hydrogenation catalysts, which are carbonyl catalysts. The mainstream types include copper-zinc-aluminum oxides, copper-zinc carbonate compounds, and new catalysts with a combination of multiple metal elements. In actual operation, although this type of catalyst has good catalytic efficiency and selectivity, it has the defect of being not resistant to hydrolysis. The main reason is that zinc oxide and aluminum oxide, etc., will combine with water to form hydroxides under high temperature and the presence of water (a small amount of water generated during the reaction process), causing the loss of the effective components of the catalyst, namely the corresponding oxides.

[0006] US20140308597A1 discloses a copper-zinc-gallium oxide catalyst. Although gallium replaces aluminum, the co-precipitated zinc oxide component still has the problem of a short catalyst cycle. The main reason is that the oxides of the three elements fail to form a spatial structure and are a mixture of a single oxide structure.

[0007] US20190076828A1 discloses a catalyst prepared by copper-zinc-magnesium co-precipitation and high-temperature treatment, which also has certain hydrolysis problems.

[0008] Research institutions in my country, such as the Shanghai Institute of the Chinese Academy of Sciences and the Dalian Institute of Chemical Physics of the Chinese Academy of Sciences, have also conducted research on the synthesis of methanol from carbon dioxide and hydrogen. The catalysts basically use copper-zinc-aluminum combination catalysts, and current research has not been able to break through the stage of industrial application.

[0009] Currently, most catalysts and methods for producing methanol from carbon dioxide have problems of low conversion rate and poor selectivity.

[0010] Although the synthesis of methanol by the reaction of carbon dioxide and hydrogen meets the requirements of green and environmentally friendly chemistry, when the synthesized methanol is further used to synthesize ethylene glycol, the prepared ethylene glycol has many impurities and the content is not low. It is usually difficult to use it directly in the synthesis of polyester. If it is directly used to synthesize polyester, the performance of the polyester is difficult to guarantee. In the prior art, ethylene glycol is usually synthesized by petrochemical method, and then used as a raw material for polyester synthesis. However, as mentioned above, this method is not green and environmentally friendly, and it should be improved when petroleum resources are at risk of depletion. Summary of the invention

[0011] The purpose of the present invention is to provide a method for preparing methanol based on carbon dioxide capture, which is green and environmentally friendly and can significantly improve the conversion rate and reaction selectivity of carbon dioxide.

[0012] Another object of the present invention is to provide a device for preparing methanol based on carbon dioxide capture, by which the conversion rate of carbon dioxide can be significantly improved.

[0013] Another object of the present invention is to provide a catalyst for catalyzing the reaction of carbon dioxide and hydrogen to prepare methanol. The use of the catalyst can significantly improve the conversion rate of carbon dioxide and the selectivity of the hydrogenation reaction.

[0014] Another object of the present invention is to provide a method for preparing ethylene glycol, which is green and environmentally friendly and can achieve low-carbon production.

[0015] Another object of the present invention is to provide a method for preparing environmentally friendly polyester, which uses ethylene glycol prepared based on carbon dioxide capture as one of the polymerization monomers, thereby achieving environmentally friendly production of polyester and ensuring that the performance of the polyester can basically achieve the performance level of polyester prepared by petrochemical ethylene glycol.

[0016] In order to achieve the above object, the technical solution adopted by the present invention is:

[0017] A method for preparing methanol, using carbon dioxide and hydrogen as raw materials, preparing methanol through hydrogenation reaction, wherein the hydrogenation reaction is sequentially carried out in three-stage fixed bed reactors, wherein the first-stage fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the second-stage fixed bed reactor is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, and the third-stage fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier and active components; the active components comprise copper oxide, zinc oxide, calcium oxide, magnesium oxide and aluminum oxide; the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier, a nano-silicon dioxide carrier, and a porous deposition catalyst layer located on the surface of the nano-silicon dioxide carrier, wherein the porous deposition catalyst layer comprises copper oxide, zirconium oxide, titanium oxide and vanadium oxide; the support carrier comprises graphite, activated carbon and a binder.

[0018] The present invention uses a new type of catalyst with a columnar porous structure. At the same time, by designing a multi-stage fixed-bed hydrogenation reactor, the equilibrium reaction of synthesizing methanol can be promoted to move in the opposite direction of the forward reaction, thereby improving the conversion rate and selectivity of carbon dioxide when synthesizing methanol from carbon dioxide. The use of staged reaction effectively increases the residence time of the mixed gas flow in the main reaction zone, and effectively improves the conversion rate of a single cycle reaction. The copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst has the ability to resist hydrolysis deactivation under the premise of having a good catalytic effect, is not affected by the moisture in the reaction by-products, and its active components, namely the oxides in the porous deposition catalyst layer, are all insoluble in water and are stable oxidized deposits.

[0019] In some embodiments, in the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the support carrier accounts for 40%-50% by weight, and the active component accounts for 50%-60% by weight.

[0020] In some embodiments, in the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the copper oxide accounts for 30%-40% of the active component, the zinc oxide accounts for 23%-30% of the active component, the calcium oxide accounts for 4%-6% of the active component, the magnesium oxide accounts for 14%-18% of the active component, and the aluminum oxide accounts for 15%-20% of the active component by weight percentage;

[0021] Preferably, the copper oxide accounts for 32%-38% of the active component, the zinc oxide accounts for 24%-28% of the active component, the calcium oxide accounts for 4.2%-5.8% of the active component, the magnesium oxide accounts for 15%-17% of the active component, and the aluminum oxide accounts for 16.0%-19.0% of the active component.

[0022] More preferably, the copper oxide accounts for 34%-36% of the active component, the zinc oxide accounts for 25%-27% of the active component, the calcium oxide accounts for 4.5%-5.5% of the active component, the magnesium oxide accounts for 15.5%-16.5% of the active component, and the aluminum oxide accounts for 17.0%-18.0% of the active component.

[0023] In some embodiments, in the copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst, the support carrier accounts for 40%-50%, the nano-silica carrier accounts for 20%-25%, and the porous deposition catalyst layer accounts for 25%-40%.

[0024] In some embodiments, in the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, the porous deposition catalyst layer is composed of 40%-50% by weight of the copper oxide, 25%-35% by weight of the zirconium oxide, 10%-15% by weight of the titanium oxide, and 10%-15% by weight of the vanadium oxide.

[0025] Preferably, the copper oxide accounts for 42%-48% of the porous deposited catalyst layer, the zirconium oxide accounts for 26%-34% of the porous deposited catalyst layer, the titanium oxide accounts for 10.8%-14.2% of the porous deposited catalyst layer, and the vanadium oxide accounts for 11.5%-13.5% of the porous deposited catalyst layer.

[0026] More preferably, the copper oxide accounts for 43.5%-46.5% of the porous deposited catalyst layer, the zirconium oxide accounts for 28%-32% of the porous deposited catalyst layer, the titanium oxide accounts for 11.5%-13.5% of the porous deposited catalyst layer, and the vanadium oxide accounts for 12%-13% of the porous deposited catalyst layer.

[0027] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst has a specific surface area of ​​125-150 m2 / g.

[0028] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst has a length of 4-8 mm.

[0029] In some embodiments, the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst has a specific surface area of ​​80-100 m 2 / g.

[0030] In some embodiments, the copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst has a length of 4-8 mm.

[0031] In some embodiments, in the support carrier, by weight percentage, the graphite accounts for 30%-35%, the activated carbon accounts for 45%-55%, and the binder accounts for 15%-20%.

[0032] In some embodiments, the graphite has a particle size of 0.2-0.3 μm.

[0033] In some embodiments, the activated carbon is coconut shell charcoal powder.

[0034] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) mixing a water-soluble zinc salt, a water-soluble magnesium salt and a water-soluble aluminum salt in the form of a solution to obtain a mixed solution; dripping an aqueous sodium hydroxide solution into the mixed solution to obtain a coprecipitation sedimentation suspension; 2) simultaneously dripping an aqueous solution of a water-soluble copper salt, an aqueous solution of a water-soluble calcium salt and an aqueous sodium hydroxide solution into the coprecipitation sedimentation suspension; 3) adding an aqueous sodium bicarbonate solution to adjust the pH value of the reaction system; heating and aging; 4) placing the reaction system in a high-pressure reactor, and under heating and stirring conditions, high-pressure blasting, dehydration treatment, and redispersion in water to form a suspension; 5) dripping tetrabutyl silicate into the suspension; 6) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating and shaping to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0035] The copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst of the present invention is a co-deposited porous nano multi-metal catalyst having excellent carbonyl hydrogenation catalytic activity and high selectivity. During high-pressure explosion, the high-pressure circulation pump is started to transport the high-temperature and high-pressure suspension to a specially designed high-pressure explosion nozzle, and the catalyst powder suspension that has completed the dehydration reaction is suddenly exploded from the high-pressure superheated condition to the normal pressure condition, and the submicron powder is exploded into nanometer powder, and the porous area rate of the powder is greatly improved.

[0036] In some embodiments, the water-soluble zinc salt, water-soluble magnesium salt, water-soluble aluminum salt, water-soluble copper salt and water-soluble calcium salt are respectively selected from sulfates, acetates or chlorides of the corresponding metal elements.

[0037] In some embodiments, in the mixed solution, the molar concentration of the water-soluble zinc salt is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0038] In some embodiments, in the mixed solution, the molar concentration of the water-soluble magnesium salt is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0039] In some embodiments, in the mixed solution, the molar concentration of the water-soluble aluminum salt is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0040] In some embodiments, the molar concentration of the sodium hydroxide aqueous solution is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0041] In some embodiments, the molar concentration of the aqueous solution of the water-soluble copper salt is 1.0-3.0 mol / L, preferably 3.0 mol / L.

[0042] In some embodiments, the molar concentration of the aqueous solution of the water-soluble calcium salt is 1.0-3.0 mol / L, preferably 0.5 mol / L.

[0043] In some embodiments, the molar concentration of the sodium bicarbonate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0044] In some embodiments, the dropping in steps 1) and 2) is performed at 70-80°C.

[0045] In some embodiments, the dropping in steps 1) and 2) is performed at a pH of 9.5-10.5.

[0046] In some embodiments, in step 3), the pH value of the system after adjustment is 9.5-10.5, preferably 10.0.

[0047] In some embodiments, the high pressure blasting in step 4) is performed by a high pressure blasting nozzle.

[0048] In some embodiments, in step 5), the dropping of tetrabutyl silicate is performed at 70-80° C. for 6-8 hours.

[0049] In some embodiments, the tetrabutyl silicate accounts for 100-150 ppm by mass of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0050] In some embodiments, in step 6), the temperature of the heating and setting is 320-350°C.

[0051] In some embodiments, the copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) synchronously titrating an aqueous solution of a water-soluble copper salt, a tetraalkyl zirconium, a tetraalkyl titanate, an aqueous solution of sodium metavanadate, an aqueous solution of sodium hydroxide, and an aqueous solution of sodium carbonate on a nano-silica carrier, and after the reaction, a porous deposition catalyst layer is formed on the nano-silica carrier; the alkyl group is a C1-6 alkyl group; 2) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating it to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0052] In some embodiments, the water-soluble copper salt is selected from one or both of copper sulfate and copper chloride.

[0053] In some embodiments, the tetraalkyl zirconium is tetraethyl zirconium.

[0054] In some embodiments, the tetraalkyl titanate is tetraisopropyl titanate.

[0055] In some embodiments, the molar concentration of the aqueous solution of the water-soluble copper salt is 1.0-3.0 mol / L, preferably 3.0 mol / L.

[0056] In some embodiments, the molar concentration of the sodium metavanadate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0057] In some embodiments, the molar concentration of the sodium hydroxide aqueous solution is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0058] In some embodiments, the molar concentration of the sodium bicarbonate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0059] In some embodiments, in step 1), the titration is performed at a pH of 9-11.

[0060] In some embodiments, in step 2), the heating treatment is performed at a temperature of 50-600° C. and for a time of 16-24 hours.

[0061] In some embodiments, the first-stage fixed bed reactor includes an inner chamber and an outer chamber; the inner chamber includes multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a tower design, and multiple groups of equalizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber and the equalizing plates of the outer chamber; and a filter is provided at the bottom of the outer chamber.

[0062] In the present invention, the aforementioned staggered design of two adjacent tower trays means that the projections of the two tower trays on the horizontal plane partially overlap. For example, an upper tower tray is fixed on one side of the inner chamber, and its horizontal length is smaller than the diameter of the inner chamber. An adjacent lower tower tray is fixed on the other side of the inner chamber, and its horizontal length is also smaller than the diameter of the inner chamber. Moreover, the projections of the two on the horizontal plane partially overlap, so that the airflow can flow between the two adjacent tower trays, thereby extending the residence time of the airflow.

[0063] In some embodiments, the effective volumes of the inner chamber and the outer chamber are the same.

[0064] In some embodiments, the residence time of the reaction gas in the inner chamber and the outer chamber is the same, so as to ensure the stability of the entire reaction in the first stage fixed bed reactor.

[0065] In some embodiments, the residence time of the raw gas in the first-stage fixed bed reactor is 135-160 s, preferably 140-155 s, and more preferably 145-150 s.

[0066] In some embodiments, after the hydrogenation reaction in the first stage fixed bed reactor is completed, the conversion rate of carbon dioxide is 38.0%-50%, preferably 39.5%-43.5%, and more preferably 40.2%-43.5%.

[0067] In some embodiments, the volume of the first stage fixed bed reactor is 135-150m 3 The volume of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 75-90m 3 .

[0068] In some embodiments, the second-stage fixed bed reactor adopts a multi-layer tray reflux design, and phase separation is completed simultaneously during the reaction process, with the bottom being a high-pressure methanol gas-liquid mixed product and the top being an unreacted mixed gas phase.

[0069] In some embodiments, the volume of the second stage fixed bed reactor is 50-58m 3 .

[0070] In some embodiments, the volume of the first stage fixed bed reactor is 2.5-3.0 times the volume of the second stage fixed bed reactor.

[0071] In some embodiments, the residence time of the reaction system in the second-stage fixed bed reactor is 35-45 s.

[0072] In some embodiments, in the second-stage fixed bed reactor, the effective self-circulation ratio of the reaction system is 3.5-6.0.

[0073] The aforementioned effective self-circulation ratio refers to the ratio of the total amount of circulating materials to the total amount of introduced materials re-added from the outside.

[0074] In some embodiments, after the hydrogenation reaction in the second stage fixed bed reactor is completed, the cumulative conversion rate of carbon dioxide is 80.4%-91.5%.

[0075] In some embodiments, the third-stage fixed bed reactor includes an inner chamber and an outer chamber; the inner chamber includes multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a tower design, and multiple groups of equalizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber and the equalizing plates of the outer chamber; and a filter is provided at the bottom of the outer chamber.

[0076] In some embodiments, the volume of the third stage fixed bed reactor is 15-20m 3 .

[0077] In some embodiments, the volume of the second stage fixed bed reactor is 2.0-4.0 times the volume of the third stage fixed bed reactor.

[0078] In some embodiments, the residence time of the reaction system in the third-stage fixed bed reactor is 60-90 seconds.

[0079] In some embodiments, after the hydrogenation reaction in the third-stage fixed bed reactor is completed, the cumulative conversion rate of carbon dioxide is 87.5%-95.0%.

[0080] In some embodiments, the temperature of the first-stage fixed bed reactor is 150-350° C., and the pressure is 5.0-20.0 MPa.

[0081] Preferably, the temperature of the first-stage fixed bed reactor is 180-300° C., and the pressure is 7.5-15 MPa.

[0082] More preferably, the temperature of the first-stage fixed bed reactor is 260-280° C., and the pressure is 8.0-10 MPa.

[0083] In some embodiments, the temperature of the second-stage fixed bed reactor is 120-240° C., and the pressure is 15.0-20.0 MPa.

[0084] Preferably, the temperature of the second-stage fixed bed reactor is 150-200° C., and the pressure is 12.5-17.5 MPa.

[0085] More preferably, the temperature of the second-stage fixed bed reactor is 160-180° C., and the pressure is 14.0-15.0 MPa.

[0086] In some embodiments, the temperature of the third stage fixed bed reactor is 150-350° C., and the pressure is 5.0-20.0 MPa.

[0087] Preferably, the temperature of the third-stage fixed bed reactor is 180-300° C., and the pressure is 7.5-15 MPa.

[0088] More preferably, the temperature of the third stage fixed bed reactor is 260-280° C., and the pressure is 8.0-10 MPa.

[0089] In some embodiments, the carbon dioxide is derived from a byproduct of a petroleum refining process.

[0090] Preferably, the volume content of carbon dioxide in the byproduct of the petroleum refining process is 80%-90%. Carbon dioxide also contains a certain amount of low molecular weight alkanes, low molecular weight olefins, water, organic low molecular weight gases containing sulfur, nitrogen, phosphorus and other impurities.

[0091] In some embodiments, the method further comprises the steps of filtering, washing with water, washing with ammonia water, removing suspended solids, and treating with a pressure swing adsorption (PSA) device for the by-products of the petroleum refining process. After these steps, the volume content of carbon dioxide is 98.0%-99.5%.

[0092] In some embodiments, after the carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor from the bottom for hydrogenation reaction. The gas flow after the reaction flows out from the bottom of the first-stage fixed bed reactor, enters the condenser for condensation, and enters the first methanol phase separation device for phase separation after decompression.

[0093] In some embodiments, the molar ratio of carbon dioxide to hydrogen is 1:3-4.5.

[0094] In some embodiments, the gas flow at the top of the first methanol phase separation device (mainly mixed components such as unreacted carbon dioxide, hydrogen, methane, carbon monoxide, water, etc.) and the added hydrogen are mixed and pressurized, and then enter the second-stage fixed bed reactor from the lower middle part. The mixed gas flow undergoes a hydrogenation reaction in the second-stage fixed bed reactor, and the liquid components after the reaction (methanol obtained by the reaction and components with heavier molecular weight) flow out from the bottom of the second-stage fixed bed reactor and enter the first methanol phase separation device for phase separation.

[0095] In some embodiments, the amount of the supplemental hydrogen accounts for 4% to 8% of the amount of hydrogen entering the first-stage fixed bed reactor.

[0096] In some embodiments, the incompletely reacted gas (whose main components are a small amount of volatile mixed gases such as carbon dioxide, hydrogen, methane, ethane, formaldehyde, etc.) is discharged from the top of the second-stage fixed bed reactor, mixed with the second added hydrogen and pressurized, and then enters the third-stage fixed bed reactor for hydrogenation reaction. The mixed gas flow after the reaction flows out from the bottom of the third-stage fixed bed reactor and enters the second methanol phase separation device for phase separation.

[0097] In some embodiments, the amount of the second additional hydrogen accounts for 0.3% to 0.6% of the amount of hydrogen entering the first-stage fixed bed reactor.

[0098] In some embodiments, the tail gas at the top of the third-stage fixed bed reactor is introduced into a pressure swing adsorption (PSA) hydrogen recovery device after decompression treatment to adsorb hydrogen, and then desorb and recover hydrogen.

[0099] In some embodiments, the recovered hydrogen is used as the source of the additional hydrogen entering the second stage fixed bed reactor and the second additional hydrogen entering the third stage fixed bed reactor. In the present invention, the unreacted mixed gas at the top of the methanol phase separation device shared by the first and second stage methanol reactors is introduced into the second stage methanol reactor after being pressurized by a compressor, and a large-scale circulation reaction mode is adopted.

[0100] In some embodiments, the tail gas after hydrogen adsorption contains a small amount of carbon dioxide, methane, ethane, formaldehyde, acetaldehyde, trace hydrogen and other components and is sent to a tail gas incineration device for treatment and discharge.

[0101] In some embodiments, the liquid crude methanol generated by the three-stage fixed bed reactor after liquefaction and separation by the first and second methanol phase separation devices can be introduced into the crude methanol storage tank for storage.

[0102] In some embodiments, the liquid crude methanol separated by the first methanol phase separation device and the second methanol phase separation device is subjected to two-stage distillation separation, and the pressure of the second stage distillation is higher than the pressure of the first stage distillation.

[0103] For the two-stage distillation separation system, the first stage distillation adopts low-pressure distillation to transport crude methanol to the bottom of the first-stage distillation tower, and methanol is extracted from the top of the distillation tower and transported to the refined methanol product tank through cooling and reflux. The heavy components at the bottom of the low-pressure distillation tower mainly contain 50%-60% methanol, and other high-boiling point by-products, which are transported to the middle of the second-stage methanol distillation tower through a circulation pump, and then high-quality methanol is further extracted from the top of the tower by distillation, and transported to the refined methanol product tank after cooling; the high-boiling point components extracted from the bottom are transported to the fusel oil storage tank as fusel oil for further processing.

[0104] The present invention also provides a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst used in the above method.

[0105] The present invention also provides a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst used in the above method.

[0106] The present invention also provides a method for preparing ethylene glycol, comprising the steps of preparing ethylene from methanol via MTO (Methanol to Olefins) technology, preparing ethylene oxide by oxidation of ethylene, and preparing ethylene glycol by hydrolysis of ethylene oxide; the preparation method also includes the step of preparing methanol by the aforementioned method for preparing methanol of the present invention.

[0107] The ethylene glycol prepared by the method has good quality and can meet the requirements of conventional polyester esterification and polymerization reactions, thereby obtaining green carbon-reduced polyester that meets the requirements of fiber spinning.

[0108] The present invention also provides a method for preparing polyethylene terephthalate, comprising the steps of sequentially subjecting terephthalic acid and ethylene glycol to a first esterification, a second esterification, a first prepolymerization, a second prepolymerization and a final polymerization; the ethylene glycol is the ethylene glycol prepared according to the aforementioned method for preparing ethylene glycol of the present invention; the preparation method further comprises the step of adding an esterification catalyst and a composite stabilizer to terephthalic acid and ethylene glycol before the first esterification step; the esterification catalyst is selected from a combination of one or more of zinc acetate, manganese acetate, potassium acetate, sodium acetate, cobalt acetate, calcium acetate and lithium acetate; the composite stabilizer comprises an amine stabilizer, sodium bisulfite and a phosphorus stabilizer.

[0109] Environmentally friendly carbon-reducing polyester can be prepared by using terephthalic acid (PTA) and ethylene glycol raw materials prepared from industrial by-product CO2 gas flow through slurry preparation, esterification reaction, and polymerization reaction. In the esterification and polymerization process, according to the type and content level of by-products of the ethylene glycol raw material, the present invention has developed an esterification catalyst and a composite stabilizer, which can realize the preparation of green carbon-reducing polyester and ensure that its performance can basically achieve the level of polyester synthesized by ethylene glycol produced by traditional petrochemical methods.

[0110] In some embodiments, the esterification catalyst is a mixture of zinc acetate, manganese acetate and lithium acetate.

[0111] In some embodiments, the mass of the esterification catalyst accounts for 100-200 ppm of the mass of the polyethylene terephthalate.

[0112] In some embodiments, the amine stabilizer is selected from a combination of one or more of triethanolamine, triethylamine, tert-butylamine and diisopropylamine; preferably triethanolamine.

[0113] In some embodiments, the phosphorus-based stabilizer is selected from a combination of one or more of triphenyl phosphite, triethyl phosphate, trimethyl phosphate, and phosphoric acid.

[0114] In some embodiments, in the mixture, the molar ratio of zinc acetate, manganese acetate and lithium acetate is 1:0.3-0.6:0.5-0.75; preferably 1:0.35-0.50:0.55-0.70, and more preferably 1:0.40-0.45:0.55-0.60.

[0115] In some embodiments, the mass of the alcohol amine stabilizer accounts for 35-50 ppm of the mass of the polyethylene terephthalate.

[0116] In some embodiments, the mass of the sodium bisulfite accounts for 15-20 ppm of the mass of the polyethylene terephthalate.

[0117] In some embodiments, the mass of the phosphorus-based stabilizer accounts for 125-150 ppm of the mass of the polyethylene terephthalate.

[0118] In some embodiments, the preparation method further comprises the step of adding a titanium-based multi-metal catalyst as a polymerization catalyst in the second esterification step.

[0119] Further, the titanium-based multi-metal catalyst can be a nano-supported solid-phase titanium-based multi-metal catalyst in CN117567730A, the full text of which is incorporated by reference into the present invention. By using this catalyst, the influence of low molecular byproducts in green EG on antimony catalysts such as ethylene glycol antimony can be avoided. Such low molecular byproducts have reducibility and can react with antimony catalysts such as ethylene glycol antimony to generate antimony precipitation, which will reduce the catalytic activity of the catalyst and cause the product hue to deteriorate, and the L value is greatly reduced. The aforementioned titanium-based multi-metal catalyst is a surface-deposited solid-phase ultrafine nano-porous catalyst, which is coated with surface silicone ester, has good dispersibility and maintains excellent stability during the polymerization process, wherein the titanium element is deposited on the carrier surface in an amorphous state of titanium dioxide, and is firmly combined with the carrier, and a part of the titanium dioxide is bonded to the carrier surface, so it has a mild catalytic effect and will not form a single substance precipitation of titanium element. Therefore, the slice hue is greatly improved, the L value is greatly improved, and the product quality is also significantly better than the product using antimony catalyst. Titanium-based multi-metal catalysts are environmentally friendly green catalysts that can further improve the green environmental protection level of polyester products.

[0120] In some embodiments, the preparation method further includes the step of adding a solid-phase tracer in the second esterification step; the solid-phase tracer is selected from a combination of one or more of hydrophilic nano-silica, γ-nano-aluminum oxide, nano-barium sulfate powder, sub-nano-scale composite calcium carbonate-magnesium carbonate, sub-nano-scale attapulgite powder and multi-element light metal zeolite nano-powder.

[0121] Although the green ethylene glycol of the present invention is derived from the capture of industrial waste gas CO2 to produce methanol, and ethylene oxide is produced to green ethylene glycol through the MTO process. However, during its application process, it is currently impossible to use chemical composition to indicate the source of the green ethylene glycol. Therefore, in order to accurately indicate the unique source of green carbon capture ethylene glycol in the production and consumption links, the present invention uses a tracer, that is, a chemically inert substance in the esterification, polymerization reaction process, and spinning production and consumption process. Within the content range of 20 to 300 ppm, its content and components can be accurately detected by instruments or chemical methods.

[0122] For the above-mentioned solid-phase tracers, an effective detection method is to determine the content of the marker through elemental emission spectroscopy. For further confirmation, the presence of the nano-marker can be confirmed by taking photos using a scanning electron microscope.

[0123] In some embodiments, the preparation method further includes the step of adding a liquid phase tracer to terephthalic acid and ethylene glycol before performing the first esterification step; the liquid phase tracer is selected from a combination of one or more of isophthalic acid, phthalic acid, trimellitic acid, pyromellitic acid, cyclohexanedicarboxylic acid, 2,2,4,4-tetramethylcyclobutanedicarboxylic acid, pentaerythritol, neopentyl glycol, 1,2-dibutanol, 2,2,4,4-tetramethylcyclobutane dimethanol and 1,4-cyclohexanedimethanol.

[0124] For the above-mentioned liquid phase tracer, a polymerized monomer with an obvious nuclear magnetic resonance effect is used, which can show the absorption peak of its structural characteristics in the nuclear magnetic resonance area. It can be used as a monomer polymerized in the macromolecular segment, and its content is 50-300ppm. It can show obvious absorption characteristic peaks in nuclear magnetic resonance, and the liquid phase marker can be combined with the solid phase marker. Through batch and content adjustment, the entire life cycle of the green ethylene glycol-based fiber can be comprehensively tracked and confirmed.

[0125] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0126] The present invention uses a new type of catalyst with a columnar porous structure, and by designing a multi-stage fixed bed hydrogenation reactor, it can promote the equilibrium reaction of synthesizing methanol to move in the opposite direction of the forward reaction, and improve the conversion rate and selectivity of carbon dioxide when synthesizing methanol from carbon dioxide. The use of staged reaction effectively increases the residence time of the mixed gas flow in the main reaction zone, and effectively improves the conversion rate of a single cycle reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0127] Figure 1 Schematic diagram of the structure of the methanol synthesis device used in the embodiment;

[0128] Figure 2 Schematic diagram of the structure of the first stage fixed bed reactor used in the embodiment;

[0129] Figure 3 Schematic diagram of the structure of the methanol distillation device used in the embodiment;

[0130] Among them, 1-first stage fixed bed reactor, 2-second stage fixed bed reactor, 3-third stage fixed bed reactor, 4-first methanol phase separation device, 5-pressure swing adsorption PSA device, 6-crude methanol storage tank, 7-low-pressure methanol distillation tower, 8-methanol reflux tank, 9-medium-pressure methanol distillation tower, 10-refined methanol storage tank, 11-fusel oil storage tank, 12-inner chamber, 13-outer chamber, a-CO2+H2, b-H2, c-tail gas, d-crude methanol, e-refined methanol, f-fusel oil. DETAILED DESCRIPTION

[0131] In the traditional synthesis of methanol through carbon dioxide hydrogenation reaction, for the high-pressure and high-temperature hydrogenation reactor, due to the limitations of materials and reaction temperature (pressure resistance 15.0Mpa, temperature 350℃), the volume of a single reactor structure should not be too large (generally based on material balance, heat calculation and safety requirements, the total volume of a 100,000-ton methanol reactor is 50-100m 3 ), so the airflow stays in the reactor for a short time. The existing methanol reactor design (the full volume of a 100,000 ton methanol reactor is approximately equal to 50m 3 ) adopts a large-volume self-circulation design for exhaust gas, which consumes a lot of energy, the residence time of the mixed gas in the catalyst area is short, the degree of single-pass reaction is low, and the overall conversion rate of carbon dioxide is limited and very low.

[0132] This patented three-stage methanol reactor adopts a reinforced design. The first-stage methanol reactor adopts a single-cycle reaction. The residence time of the initial mixed gas in the first-stage reactor is greatly extended by 3.0-5.5 times. Sufficient residence time effectively improves the reaction conversion rate.

[0133] One of the innovative points of the present invention is the use of a hydrolysis-resistant copper-zirconium-titanium-vanadium deposition-type oxide hydrogenation catalyst in a secondary methanol reactor, which has the effects of hydrolysis resistance and resistance to hydrolysis deactivation. The catalyst is developed and designed based on the characteristics of the reaction gas phase components after the reaction in the primary hydrogenation reactor is completed and separated by a methanol phase separation device. The reaction temperature and pressure of the catalyst are different from those of the first-stage methanol reactor. The hydrogenation reaction can be completed at a lower temperature and a higher pressure, and the mixed phase separation is completed by gas-liquid separation. The crude methanol and high-boiling point by-products are introduced into the crude methanol storage tank from the bottom, and the gas phase part is led out from the top and sent to the third-stage methanol reactor. Since the second-stage reactor uses the aforementioned hydrolysis-resistant hydrogenation catalyst, the carbon dioxide that failed to be completed in the first-stage methanol reactor is further reacted with hydrogen, and the degree of carbon dioxide hydrogenation reaction is further improved.

[0134] The third-stage hydrogenation reactor is an auxiliary system that further improves the carbon dioxide conversion rate based on the completion of the main reaction in the first and second-stage reactors. Because the by-product content in the tail gas from the top of the second-stage methanol reactor is further increased, the catalyst used in the third-stage reactor is the same as that in the first stage.

[0135] One of the innovative points of the present invention is the first-stage methanol reactor of the main reaction device. The raw material inlet is a pure carbon dioxide and hydrogen mixed gas. Compared with the single-stage methanol reactor, the unreacted recycled gas is injected into the mixed gas inlet, which eliminates the influence of reaction by-products on the catalyst activity, greatly prolongs the service life of the hydrogenation catalyst, and improves the efficiency of the main reaction of the first-stage methanol reactor. Especially the influence of water in the by-products on the catalyst. Another advantage of the three-stage methanol reactor is that the staged reaction is used to effectively increase the residence time of the mixed gas flow in the main reaction zone, and effectively improve the conversion rate of a single cycle reaction. The present invention introduces the unreacted mixed gas at the top of the methanol phase separation device shared by the first-stage and second-stage methanol reactors into the second-stage methanol reactor after pressurization by a compressor, and adopts a large-scale circulation reaction mode.

[0136] One of the innovative points of the present invention is the specific structural setting of the first-stage fixed bed reactor. Specifically, carbon dioxide gas and hydrogen are compressed and mixed and then injected into the system from the bottom of the inner chamber of the first-stage fixed bed reactor. The inner chamber of the reactor is designed as a multi-layer tray design. For each stage of the tray, the reaction mixed gas enters from a corner of the bottom of the tray, flows horizontally along the tray, and enters the upper tray from the upper channel diagonally opposite the bottom corner, and circulates to the top of the inner chamber. This design effectively improves the contact residence time of the mixed gas and the catalyst, and improves the reaction uniformity and reaction efficiency. The outer chamber is designed as a tower design. After the mixed gas reacts in the inner chamber, it is collected at the top of the reactor and then enters the outer chamber for reaction. The mixed gas flow in the outer chamber flows from top to bottom to the bottom of the reactor, and after being collected, it is introduced into the first methanol phase separation device through heat exchange and cooling. Multiple groups of homogenizing disks are designed at the top, middle and bottom of the outer chamber, and catalyst particles are filled between the homogenizing disks. Each homogenizing disk first collects gas, and then guides it to the next layer through the homogenizing design channel to ensure that the mixed gas flow passes through multiple catalyst layers in the tower body evenly. A filter screen is designed at the bottom of the outer chamber to prevent catalyst particles from entering the bottom outlet.

[0137] The second-stage methanol reactor is designed to have a mixed gas phase flow rate of 50,000-150,000 tons. Its effective full volume is 50%-65% of the first-stage methanol reactor. It adopts a multi-layer tower tray reflux design. The reaction process completes phase separation simultaneously. The bottom is a high-pressure methanol gas-liquid mixed product, and the top is an unreacted mixed gas phase.

[0138] The third-stage methanol reactor adopts the same design as the first-stage methanol reactor, and its device capacity is 4000-8000 tons of mixed gas phase flow. The mixed gas after reaction is extracted from the bottom and then sent to the second methanol phase separation device designed separately. After decompression separation, the liquid phase is transported to the crude methanol storage tank, and the gas phase is led to the pressure swing adsorption PSA device. After the unreacted hydrogen is recovered, it is sent to the waste gas treatment system for harmless treatment and emptying.

[0139] Unlike ethylene glycol EG prepared by petrochemical ethylene engineering, the green ethylene glycol prepared by this patent has different impurities and byproducts in its components, especially in the types and contents of low molecular aldehydes and organic acids. Specifically, the ethylene glycol prepared by the present invention has a higher acetaldehyde content, a lower 1,4-dioxane content, a slightly higher low molecular carboxylic acid content than petrochemical ethylene glycol, and a slightly lower ultraviolet light transmittance at 220nm and 250nm than petrochemical ethylene glycol. This will lead to a decrease in the hue L value of the PET product, a lower a value, and a higher b value during the esterification and polymerization reaction process when the subsequent polymerization is used to synthesize PET. And its esterification reaction rate is significantly lower than that of petrochemical ethylene glycol. Under the same esterification conditions, the esterification rate of the green EG of the present invention in the first esterification kettle decreases by 3%-5%, and the esterification rate of the second esterification kettle decreases by 2.2%-4.0%.

[0140] In this regard, one of the innovative points of the present invention is to add an esterification catalyst to ensure that the esterification reaction proceeds smoothly. The manganese element in the manganese acetate in the esterification catalyst has reducing properties and can react with metal compounds with oxidizing properties during the reaction process, and can also react with the oxidant component in the reaction system, thereby avoiding the deactivation of the effective active center components of antimony-based and titanium-based catalysts, thereby ensuring the good esterification reaction state of the new green ethylene glycol. In addition, during polymerization, an alcohol amine stabilizer with a complexing function is combined with sodium bisulfite to form a composite stabilizer with a phosphorus stabilizer. Among them, the alcohol amine stabilizer can effectively complex and seal the heavy metal element ions and reducing low-molecular organic impurities in the green ethylene glycol, and sodium bisulfite can seal the active aldehyde and ketone by-products, thereby reducing the level of side reactions produced by this component, and the phosphorus stabilizer can control the thermal degradation reaction during the esterification and polymerization reactions.

[0141] The technology for preparing methanol by hydrogenating carbon dioxide of the present invention adopts a brand-new design concept: 1) a high-strength titanium plate is used as a material for processing a methanol reactor, which effectively increases the total volume of a primary methanol reactor and greatly increases the residence time of a mixed gas of carbon dioxide and hydrogen in a fixed bed of a methanol reactor; 2) a unique inner chamber gas phase flow channel design and an outer chamber homogenization design make the reaction more uniform; 3) the primary methanol reactor does not adopt tail gas circulation, thereby improving the primary reaction conversion rate; 4) the process flow is further optimized through the high-proportion self-circulation technology of a secondary methanol reactor; 5) combined with a third-stage methanol synthesis reactor, a more reasonable process flow technology is used to extend the service life of the catalyst, improve the conversion efficiency of preparing methanol by hydrogenating carbon dioxide; and the use of catalysts of different components further improves the operating stability of the device from the material reaction level.

[0142] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions used in the examples can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments. Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art.

[0143] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0144] The present invention is further described below in conjunction with the accompanying drawings and preferred embodiments of the present invention. The orientations and positional relationships described in the present invention are only for the convenience of describing the invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, only have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0145] like Figure 1-3 As shown, the device system for preparing methanol includes Figure 1 A three-stage fixed-bed reactor for methanol synthesis, and Figure 2 The first stage fixed bed reactor 1 is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the second stage fixed bed reactor 2 is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, and the third stage fixed bed reactor 3 is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0146] like Figure 2 As shown, the first-stage fixed bed reactor 1 includes an inner chamber 12 and an outer chamber 13; the inner chamber 12 includes multiple layers of horizontally arranged tower plates (not shown, what is shown is the path of the airflow, and due to the staggered design of the tower plates, the path of the airflow is diagonal); two adjacent tower plates are staggered; the outer chamber 13 is designed as a tower design, and multiple groups of equalizing plates are designed at the top, middle and bottom of the outer chamber 13 (not shown, what is shown is the path of the airflow, and due to the staggered design of the tower plates, the path of the airflow is diagonal); the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber 12 and the equalizing plates of the outer chamber 13; a filter screen is arranged at the bottom of the outer chamber 13 (not shown in the figure).

[0147] The second-stage fixed bed reactor 2 adopts a multi-layer tray 14 reflux design, and phase separation is completed during the reaction process. The bottom is a high-pressure methanol gas-liquid phase mixed product, and the top is an unreacted mixed gas phase.

[0148] The third-stage fixed bed reactor 3 adopts the same structure as the first-stage fixed bed reactor 1 .

[0149] like Figure 1 As shown, after carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor 1 from the bottom for hydrogenation reaction. The reacted gas flow flows out from the bottom of the first-stage fixed bed reactor 1, enters the condenser for condensation, and enters the first methanol phase separation device 4 for phase separation after decompression. The gas flow at the top of the first methanol phase separation device 4 and the added hydrogen are mixed and pressurized, and then enter the second-stage fixed bed reactor 2 from the middle and lower part. The mixed gas flow undergoes hydrogenation reaction in the second-stage fixed bed reactor 2. The liquid component after the reaction flows out from the bottom of the second-stage fixed bed reactor 2 and enters the first methanol phase separation device 4 for phase separation. The unreacted gas is extracted from the top of the second-stage fixed bed reactor 2, mixed with the second added hydrogen and pressurized, and then enters the third-stage fixed bed reactor 3 for hydrogenation reaction. The reacted gas flow flows out from the bottom of the third-stage fixed bed reactor 3 and enters the second methanol phase separation device for phase separation. The tail gas at the top of the third-stage fixed bed reactor 3 is introduced into the pressure swing adsorption PSA device 5 after decompression treatment, and hydrogen is adsorbed, desorbed, and hydrogen is recovered. The recovered hydrogen is used as the supplementary hydrogen entering the second-stage fixed bed reactor 2 and as the source of the second supplementary hydrogen entering the third-stage fixed bed reactor 3. The liquefied liquid crude methanol generated by the third-stage fixed bed reactor and separated by the first and second methanol phase separation devices can be introduced into the crude methanol storage tank 6 for storage.

[0150] like Figure 3 As shown, the liquid crude methanol separated by the first methanol phase separation device 4 and the second methanol phase separation device is subjected to two-stage distillation separation, and the pressure of the second stage distillation is higher than that of the first stage distillation. For the two-stage distillation separation system, the first stage distillation adopts low-pressure distillation, and the crude methanol is transported to the bottom of the low-pressure methanol distillation tower 7, and the methanol is extracted from the top of the distillation tower and transported to the refined methanol storage tank 10 after cooling and reflux. The heavy components at the bottom of the low-pressure methanol distillation tower 7 are mainly 50%-60% methanol, and other high-boiling point by-products, which are transported to the middle of the medium-pressure methanol distillation tower 9 through a circulation pump, and then high-quality methanol is further extracted from the top of the tower through distillation, and transported to the refined methanol storage tank 10 after cooling; the high-boiling point components extracted from the bottom are transported as fusel oil to the fusel oil storage tank 11 for further processing.

[0151] Preparation Example 1

[0152] This preparation example provides a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, and its preparation method is as follows:

[0153] First, prepare 1.0M aqueous solution of copper sulfate, zinc sulfate, calcium chloride, magnesium sulfate and aluminum sulfate, filter with quantitative filter paper and set aside. Prepare 1.0M sodium hydroxide aqueous solution and 0.5M sodium bicarbonate aqueous solution. Mix the zinc sulfate aqueous solution, magnesium sulfate aqueous solution and aluminum sulfate aqueous solution at a molar ratio of 1.0:1.0:0.75, and then add the above sodium hydroxide aqueous solution to the mixed solution under stirring for 4.0 hours, control the molar ratio of metal ions to hydroxide to meet the stoichiometric ratio, and prepare a coprecipitation suspension. Control the temperature of the system to 70°C during the addition, and continue to stabilize for 2.0 hours after the addition is completed.

[0154] The copper sulfate aqueous solution and the calcium chloride aqueous solution are added to the above-mentioned coprecipitation suspension in a molar ratio of 1.5:1.8, and the sodium hydroxide aqueous solution prepared above is added simultaneously in a stoichiometric ratio. The dropping time is controlled to be 4 hours, and the pH value of the system is controlled to be about 10 during the dropping process. After the dropwise addition is completed, the pH value of the suspension is adjusted to 10.0 with an aqueous sodium bicarbonate solution. The suspension is heated to 90°C and stabilized for 1.0 hours. The suspension is then transferred to a 2.5MPa pressure-resistant stainless steel reactor, heated to 220°C under high-speed stirring conditions, and stirred for 5.0 hours, and then the high-pressure circulation pump is started to transport the suspension to a specially designed high-pressure blasting nozzle. The suspension is first dehydrated in the high-pressure blasting nozzle under high-pressure overheating conditions, and then suddenly exploded to normal pressure conditions. In this process, the submicron powder in the suspension is exploded into nano-scale powder, and the porosity and specific surface area of ​​the powder are greatly improved.

[0155] The nano powder after blasting is partially dehydrated, and after washing away the soluble components with distilled water, a water suspension with a concentration of 10% is formed under stirring conditions. Tetrabutyl silicate accounting for 150ppm of the powder mass is added to the water suspension at a temperature of 80°C, and the dropping time is controlled to be 6 hours. After the dropping is completed, it is aged for 2.0 hours. The water is filtered to remove the water, and submicron graphite, coconut shell carbon powder, and adhesive (the mass ratio of the three is 3:5:2) are added to the filter cake as a supporting carrier to prepare a columnar porous granular material, which is dried and shaped at 320°C to obtain a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0156] The specific surface area of ​​the catalyst is 125 m 2 / g, cylindrical, and the length of the column is 4.0mm.

[0157] In the catalyst, the support carrier accounts for 40wt%, the active component accounts for 60wt%, and in the active component, according to mass percentage, copper oxide accounts for 35.0%, zinc oxide accounts for 26.0%, calcium oxide accounts for 4.2%, magnesium oxide accounts for 16.8%, and aluminum oxide accounts for 18.0%.

[0158] Preparation Example 2

[0159] This preparation example provides a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, and its preparation method is as follows:

[0160] Nano-silica was used as a carrier, and the prepared copper sulfate aqueous solution (concentration of 3.0 mol / L), tetraethyl zirconium, tetraisopropyl titanate, sodium metavanadate aqueous solution (concentration of 2.0 mol / L), sodium hydroxide aqueous solution (concentration of 2.5 mol / L), and sodium carbonate aqueous solution (concentration of 2.0 mol / L) were simultaneously added to the nano-silica. The pH value of the system was strictly controlled to be 10 during the addition process. The precipitate formed by the reaction of the above four metal ions with the alkali solution was deposited on the surface of the nano-silica carrier to form a porous deposition catalyst layer. The suspension was then filtered, washed with water, and pressed into columnar porous catalyst particles with submicron graphite, coconut shell carbon powder, and adhesive (the mass ratio of the three was 3:5:2, as a supporting carrier), and then sent to a muffle furnace for treatment at 600°C for 16 hours to obtain a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst. The catalyst surface has a porous structure.

[0161] The specific surface area of ​​the catalyst is 100 m 2 / g, cylindrical, and the length of the column is 5.0mm.

[0162] The catalyst comprises 40 wt% of a support carrier, 20 wt% of a nano-silicon dioxide carrier, and 40 wt% of an active component porous deposition catalyst layer. Among the active components, according to mass percentage, copper oxide accounts for 45%, zirconium oxide accounts for 30%, titanium oxide accounts for 12.0%, and vanadium oxide accounts for 13.0%.

[0163] Comparative Preparation Example 1

[0164] This comparative preparation example provides a hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 1, except that the raw material does not contain calcium chloride aqueous solution.

[0165] Comparative Preparation Example 2

[0166] This comparative preparation example provides a hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 1, except that the raw material does not contain an aqueous solution of magnesium sulfate.

[0167] Comparative Preparation Example 3

[0168] This comparative preparation example provides a deposited hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 2, except that the raw material does not contain tetraethyl zirconium.

[0169] Comparative Preparation Example 4

[0170] This comparative preparation example provides a deposited hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 2, except that the raw material does not contain a sodium metavanadate aqueous solution.

[0171] Example 1

[0172] This embodiment provides a method for preparing methanol, which is as follows:

[0173] Taking the 200,000 tons / year CO2 hydrogenation to methanol unit as an example, the sources and quality indicators of its raw materials hydrogen and CO2 are as follows:

[0174] Hydrogen: When green power generation is used as energy to produce propylene using methanol to olefins technology (MTO process), hydrogen is a byproduct. Its quality indicators (hydrogen content and impurity content) and process parameter information are shown in Table 1:

[0175] Table 1. Hydrogen raw material indicators and process parameters

[0176]

[0177] Carbon dioxide: The high-concentration carbon dioxide gas stream (quality indicators are shown in Table 2 below) generated during petroleum refining is recovered. First, the carbon dioxide waste gas is captured, compressed, concentrated (pressure swing adsorption PSA device), desulfurized, and denitrified to prepare a carbon dioxide raw gas with a volume content of more than 98.0%;

[0178] Table 2. Carbon dioxide raw material indicators and process parameters

[0179]

[0180] The purified carbon dioxide gas is mixed with hydrogen, then pressurized to 10.0MPa, and then heated to 265°C. It is transported to the inner chamber of the first-stage methanol reactor (first-stage fixed-bed reactor), and the mixed gas flows through the inner chamber catalyst fixed bed, and then reaches the top of the methanol reactor tower, and flows evenly from top to bottom through the top outer chamber homogenizer, passes through the outer chamber multilayer catalyst fixed bed and gas homogenizer, and completes the first-stage circulation process catalytic hydrogenation reaction. The mixed gas is transported from the bottom of the outer chamber through the heat exchange and pressure reduction equipment to the first methanol phase separation device. The catalyst loaded in the above inner chamber and outer chamber is the catalyst of Preparation Example 1. In the first-stage methanol reactor, the total residence time of the carbon dioxide and hydrogen mixed phase is 145 seconds. The result is that the carbon dioxide conversion rate is 40.25% and the reaction selectivity is 97.0%.

[0181] The temperature is further reduced and refluxed in the first methanol phase separation device, and heavy components such as crude methanol and water generated by the reaction are collected from the bottom and then transported to the crude methanol intermediate tank.

[0182] The unreacted mixed gas at the top of the first methanol phase separation device is pressurized and heated (temperature raised to 180°C, pressure increased to 15.0MPa) by a compressor and a heat exchanger, and then transported to the second-stage methanol reactor (second-stage fixed bed reactor). The second-stage methanol reactor adopts a design structure different from that of the first-stage reactor. The gas-liquid phase unreacted mixed gas, crude methanol, water and high-boiling point by-products are discharged from the bottom and transported to the first methanol phase separation device for separation.

[0183] The mixed gas from the first and second stage methanol reactors is combined at the top of the first methanol phase separation device and circulated to the second stage methanol reactor through a compressor; the unreacted gas phase components are taken out from the top and directly transported to the third stage methanol reactor (third stage fixed bed reactor) through a compressor.

[0184] The second-stage methanol reactor adopts a large flux self-circulation mode to improve the reaction efficiency. The reactor is filled with the catalyst of Preparation Example 2. The residence time of the mixed phase in the second-stage methanol reactor is 35 seconds, and the effective self-circulation ratio is 3.5 times. After the second-stage methanol reactor, the cumulative conversion rate of carbon dioxide is 85.0%;

[0185] The unreacted mixed gas extracted from the top of the second-stage methanol reactor is compressed and counted into the third-stage methanol reactor. The third-stage methanol reactor adopts the same structural setting as the first-stage methanol reactor and uses the same catalyst of Preparation Example 1. After the mixed gas is catalytically hydrogenated in the third-stage methanol reactor, it is introduced into the separately designed supporting second methanol phase separation device for separation. The liquid crude methanol at the bottom of the separator is merged into the crude methanol storage tank, and the top tail gas is introduced into the PSA hydrogen recovery device after decompression treatment. The recovered hydrogen is desorbed and merged into the carbon dioxide pipeline mixed introduction system of the second-stage methanol reactor. The tail gas after hydrogen adsorption contains a small amount of carbon dioxide, methane, ethane, formaldehyde, acetaldehyde, trace hydrogen and other components, which are sent to the tail gas incineration device for treatment and venting. The liquefied crude methanol generated by the third-stage methanol reactor is introduced into the crude methanol storage tank. In the third-stage methanol reactor, the residence time of the mixed phase is 60 seconds. After the third-stage methanol reactor, the cumulative conversion rate of carbon dioxide is 94.9%.

[0186] The crude methanol produced from the first, second and third methanol reactors is collected in the crude methanol storage tank and then transported to the distillation system. After two-stage distillation, refined methanol is produced from the top of the first low-pressure methanol distillation tower, and methanol, water and high-boiling point by-products are produced from the bottom. The components are heated and gasified and transported to the second medium-pressure distillation tower. After treatment in the second distillation tower, refined methanol is produced from the top, and the heavy components at the bottom are refluxed to separate the reaction water and send it to the water treatment device for treatment. The remaining fusel oil after dehydration is sent to the fusel oil storage tank for storage and treatment. The tail gas of the device is collected in the tail gas treatment device, and discharged after harmless treatment. The refined methanol product distilled from the two-stage distillation tower is collected in the refined methanol storage tank. Its product indicators are shown in Table 3 below:

[0187] Table 3. Methanol product indicators (GB 338-2011)

[0188]

[0189] For the 200,000 tons / year carbon dioxide hydrogenation to methanol project in this embodiment, the carbon dioxide conversion rate is 94.9%, and the material balance data of the device are shown in Table 4 below.

[0190] Table 4. Material balance table of project process equipment

[0191]

[0192] Comparative Example 1

[0193] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalysts in the first-stage fixed bed reactor and the third-stage fixed bed reactor are replaced with the catalysts in Comparative Preparation Example 1. As a result, the cumulative conversion rate of carbon dioxide is 91.8%.

[0194] Comparative Example 2

[0195] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalysts in the first-stage fixed bed reactor and the third-stage fixed bed reactor are replaced with the catalysts in Comparative Preparation Example 2. As a result, the cumulative conversion rate of carbon dioxide is 92.2%.

[0196] Comparative Example 3

[0197] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalyst in the second-stage fixed bed reactor is replaced with the catalyst of Comparative Preparation Example 3. As a result, the cumulative conversion rate of carbon dioxide is 90.6%.

[0198] Comparative Example 4

[0199] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalyst in the second-stage fixed bed reactor is replaced with the catalyst of Comparative Preparation Example 4. As a result, the cumulative conversion rate of carbon dioxide is 88.7%.

[0200] Example 2

[0201] This embodiment provides a method for preparing green ethylene glycol, which is as follows:

[0202] The green refined methanol prepared in Example 1 is transported to the MTO unit for preparing olefins from methanol. In the MTO unit, the green refined methanol first prepares ethylene, and then the green ethylene is oxidized to prepare green ethylene oxide, and the ethylene oxide is hydrolyzed to prepare green ethylene glycol. The process of preparing green ethylene glycol from green methanol has been widely used in the methanol chemical industry. This example adopts the conventional implementation method of the chemical industry. The indicators of the green ethylene glycol finally obtained are shown in Table 5 below.

[0203] It meets the requirements of GB / T4649-2018 and the quality requirements of polyester-grade ethylene glycol raw materials. However, compared with petrochemical ethylene glycol, its ultraviolet light transmittance at 220nm and 250nm meets the national quality requirements, but is lower than that of petrochemical ethylene glycol. The reason is that the content of low molecular aldehydes, carboxylic acids and low molecular carboxylic acid esters, and alcohol by-products in this green ethylene glycol is higher than that of petrochemical ethylene glycol.

[0204] Table 5. Performance indicators of green ethylene glycol

[0205]

[0206] Example 3

[0207] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is as follows:

[0208] The 100% green ethylene glycol prepared in the above Example 2 was used as the polyester raw material, and polymerization spinning was carried out on a 50,000 tons / year continuous polymerization melt direct spinning device.

[0209] Device capacity: 150t / d, ultra-low temperature five-reactor process design, melt direct spinning.

[0210] The purified terephthalic acid PTA and green ethylene glycol EG are prepared into slurry at a molar ratio of 1:1.135, and the prepared esterification catalyst: a mixture of zinc acetate, manganese acetate, and lithium acetate (the molar ratio of the three is 1:0.3:0.5) is injected into the slurry tank, and the total amount of esterification catalyst added is controlled to be 100ppm of PET. The injection port is designed in the slurry conveying pipeline, and the prepared composite stabilizer is injected into the slurry. The composition of the composite stabilizer is triethanolamine, sodium bisulfite, and triphenyl phosphite. Among them, the amount of triethanolamine accounts for 50ppm of the mass of PET, the amount of sodium bisulfite accounts for 20ppm of the mass of PET, and the amount of triphenyl phosphite accounts for 150ppm of the mass of PET.

[0211] After the slurry is mixed evenly, it is transported to the first esterification kettle, where a preliminary esterification reaction is carried out. The temperature of the first esterification kettle is controlled at 256-258°C, the pressure is 75KPa, and the esterification rate of the first esterification kettle is controlled at 90%-91.5%.

[0212] After the melt reaction in the first esterification kettle is completed, the second esterification kettle is introduced. The second esterification kettle is of multi-chamber design and is divided into three esterification reaction chambers. The outlet reaction temperature of the second esterification kettle is 260-262°C. The prepared nano barium sulfate tracer (barium sulfate suspension in ethylene glycol, with a mass concentration of 5% and a barium sulfate particle size of 50nm) is added from the first chamber of the second esterification kettle, and the amount added is controlled. In terms of barium sulfate, it accounts for 50ppm of the mass of PET. As a marker, the entire life cycle of the green carbon-reducing polyester can be tracked. A titanium-based multi-metal catalyst (the catalyst of Example 1 of CN117567730A) is added from the second esterification chamber, wherein the titanium element concentration is 8ppm of the mass of PET. A liquid matting agent is added to the third chamber of the second esterification kettle, and the content is 0.3% of the mass of PET.

[0213] The melt after the esterification reaction in the second esterification reactor has an esterification rate of 96.5-97.8%, which is introduced into the first prepolymerization reactor. The reaction temperature of the first prepolymerization reactor is controlled at 269-271°C and the vacuum degree is 10.0-12.0KPa. The melt after the initial polymerization reaction in the first prepolymerization reactor is introduced into the second prepolymerization reactor to further complete the prepolymerization reaction. The second prepolymerization reactor is a uniaxial disc reactor. The reaction temperature is controlled at 273-275°C and the vacuum degree is 1.0-1.3KPa. The intrinsic viscosity of the prepolymer is controlled at 0.240-0.285 (benzene Phenol: tetrachloroethane, measured in a mixed solvent of 3:2); the melt after the prepolymerization reaction is transported to the final polymerization kettle through the prepolymer delivery pump and the prepolymerization filter. The final polymerization reactor is a front and rear double-axis disc reactor, and the outlet reaction temperature is controlled at 280-282°C, and the vacuum degree is 150-175Pa; the outlet intrinsic viscosity is controlled at 0.640-0.645 (phenol: tetrachloroethane, measured in a mixed solvent of 3:2), and the melt is transported to the direct spinning workshop through the melt delivery pump to spin various specifications of green carbon-reduced polyester fibers. The process parameters are shown in Table 6 below.

[0214] Example 4

[0215] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that in Embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and the amount of the tracer barium sulfate added to the esterification two-reactor one-chamber is increased to 100 ppm.

[0216] Example 5

[0217] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 60 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and 50 ppm of nano barium sulfate is also added to the second esterification kettle. All are calculated relative to the mass of PET.

[0218] Example 6

[0219] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 80 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and nano barium sulfate is also added to the second esterification kettle, but the amount is 80 ppm. All are calculated relative to the mass of PET.

[0220] Example 7

[0221] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 75 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and 100 ppm of sub-nano composite calcium carbonate-magnesium carbonate (including 40 ppm of calcium and 60 ppm of magnesium) is added to the second esterification kettle. All are calculated relative to the mass of PET.

[0222] Example 8

[0223] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 75 ppm of pentaerythritol is added to the pulping kettle, and 100 ppm of sub-nano composite calcium carbonate-magnesium carbonate (including 40 ppm of calcium and 60 ppm of magnesium) is added to the second esterification kettle. All are calculated relative to the mass of PET.

[0224] Table 6 Process parameters

[0225]

[0226] Comparative Example 5

[0227] The esterification and polymerization reactions are basically the same as those in Example 3, except that no esterification catalyst, tracking agent or composite stabilizer is added.

[0228] Comparative Example 6

[0229] The esterification and polymerization reactions are basically the same as those in Example 2, except that an esterification catalyst is added, and no tracking agent or composite stabilizer is added.

[0230] Comparative Example 7

[0231] The esterification and polymerization reactions are basically the same as in Example 2, except that ethylene glycol antimony catalyst is used, and no tracer, esterification catalyst, or composite stabilizer is added.

[0232] Comparative Example 8

[0233] The polymerization monomers used are EG and PTA obtained through petrochemical process, and the esterification and polymerization reactions are basically the same as those in Example 2, except that ethylene glycol antimony catalyst is used, and no tracer, esterification catalyst or composite stabilizer is added.

[0234] The use of each additive is shown in Table 7 below.

[0235] Table 7 Use of additives

[0236]

[0237] The semi-dull PET polyester prepared in the above-mentioned embodiments and comparative examples was subjected to performance tests, as shown in Table 8 below, wherein the intrinsic viscosity was measured in a mixed solvent of phenol:tetrachloroethane, 3:2.

[0238] Table 8 Properties of Semi-matte PET Polyester

[0239]

[0240] As can be seen from Table 8, compared with the petrochemical EG raw material (Comparative Example 8), the indicators of polyester prepared by green EG are obviously different from those of polyester prepared by petrochemical EG, mainly because the ethylene glycol produced by preparing methanol through hydrogenation of carbon dioxide has higher by-products than the petrochemical ethylene glycol. However, after adding targeted esterification catalysts and composite stabilizers, the indicators of the present invention are basically close to those of petrochemical polyester.

[0241] Through the melt direct spinning process, FDY fibers with specifications such as 83.3dtex / 144f and 55.5dtex / 72f were spun. The green carbon-reduced polyester fiber prepared with green ethylene glycol meets the market's post-application requirements and is basically the same as the polyester fiber synthesized with ethylene glycol from petrochemical methods.

[0242] Table 9 below shows the fiber indicators of 83.3dtex / 144fFDY.

[0243] Table 9 Physical and chemical indicators of 83.3dtex / 144fFDY fiber

[0244]

[0245] Table 10 below shows the quality indicators of 55.5dtex / 72f FDY fiber.

[0246] Table 10 Physical and chemical indicators of 55.5dtex / 72f FDY fiber

[0247]

[0248]

[0249] The fibers are woven into fabrics, and after printing and dyeing, the fabrics are traced and tested. The test results are shown in Table 11:

[0250] Table 11 Fabric tracking test

[0251]

[0252] It can be seen that the above-mentioned tracers can be used for green tracking.

[0253] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing methanol, using carbon dioxide and hydrogen as raw materials to prepare methanol through a hydrogenation reaction, characterized in that: The hydrogenation reaction is carried out in three fixed bed reactors in sequence, wherein the first fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the second fixed bed reactor is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, and the third fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier and an active component; the active component comprises copper oxide, zinc oxide, calcium oxide, magnesium oxide and aluminum oxide; the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier, a nano-silica carrier, and a porous deposition catalyst layer located on the surface of the nano-silica carrier, wherein the porous deposition catalyst layer comprises copper oxide, zirconium oxide, titanium oxide and vanadium oxide; the support carrier comprises graphite, activated carbon and a binder; The copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) mixing a water-soluble zinc salt, a water-soluble magnesium salt and a water-soluble aluminum salt in the form of a solution to obtain a mixed solution; and dripping a sodium hydroxide aqueous solution into the mixed solution to obtain a coprecipitation suspension; 2) simultaneously adding a water-soluble copper salt aqueous solution, a water-soluble calcium salt aqueous solution and a sodium hydroxide aqueous solution to the coprecipitation suspension; 3) adding a sodium bicarbonate aqueous solution to adjust the pH value of the reaction system; heating and aging; 4) placing the reaction system in a high-pressure reactor, and subjecting the reaction system to high-pressure blasting, dehydration treatment, and redispersion in water to form a suspension under heating and stirring conditions; 5) adding tetrabutyl silicate dropwise to the suspension; 6) filtering, adding graphite, activated carbon and a binder to the filter cake, heating and setting, and obtaining the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst; The copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) synchronously titrating an aqueous solution of a water-soluble copper salt, tetraalkyl zirconium, tetraalkyl titanate, an aqueous solution of sodium metavanadate, an aqueous solution of sodium hydroxide and an aqueous solution of sodium carbonate on a nano-silica carrier, and forming a porous deposition catalyst layer on the nano-silica carrier after reaction; the alkyl group is a C1-6 alkyl group; 2) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating treatment to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

2. The method for preparing methanol according to claim 1, characterized in that: In the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the support carrier accounts for 40%-50% by weight, and the active component accounts for 50%-60% by weight; and / or, in the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, the support carrier accounts for 40%-50% by weight, the nano-silica carrier accounts for 20%-25%, and the porous deposition catalyst layer accounts for 25%-40%.

3. The method for preparing methanol according to claim 2, characterized in that: In the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, according to weight percentage, the copper oxide accounts for 30%-40% of the active components, the zinc oxide accounts for 23%-30% of the active components, the calcium oxide accounts for 4%-6% of the active components, the magnesium oxide accounts for 14%-18% of the active components, and the aluminum oxide accounts for 15%-20% of the active components; and / or, in the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, according to weight percentage, the copper oxide accounts for 40%-50% of the porous deposition catalyst layer, the zirconium oxide accounts for 25%-35% of the porous deposition catalyst layer, the titanium oxide accounts for 10%-15% of the porous deposition catalyst layer, and the vanadium oxide accounts for 10%-15% of the porous deposition catalyst layer.

4. The method for preparing methanol according to claim 1, characterized in that: The specific surface area of ​​the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 125-150m 2 / g; and / or, the length of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 4-8mm; and / or, the specific surface area of ​​the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is 80-100m 2 / g; and / or, the length of the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is 4-8mm.

5. The method for preparing methanol according to claim 1, characterized in that: In the support carrier, according to weight percentage, the graphite accounts for 30%-35%, the activated carbon accounts for 45%-55%, and the binder accounts for 15%-20%; and / or the particle size of the graphite is 0.2-0.3 μm; and / or the activated carbon is coconut shell carbon powder.

6. The method for preparing methanol according to claim 1, characterized in that: The water-soluble zinc salt, water-soluble magnesium salt, water-soluble aluminum salt, water-soluble copper salt and water-soluble calcium salt are respectively selected from sulfates, acetates or chlorides of corresponding metal elements.

7. The method for preparing methanol according to claim 1, characterized in that: In the mixed solution, the molar concentration of the water-soluble zinc salt is 1.0-3.0 mol / L; and / or, in the mixed solution, the molar concentration of the water-soluble magnesium salt is 1.0-3.0 mol / L; and / or, in the mixed solution, the molar concentration of the water-soluble aluminum salt is 1.0-3.0 mol / L; and / or, the molar concentration of the sodium hydroxide aqueous solution is 1.0-3.0 mol / L; and / or, the molar concentration of the aqueous solution of the water-soluble copper salt is 1.0-3.0 mol / L; and / or, the molar concentration of the aqueous solution of the water-soluble calcium salt is 0.5-3.0 mol / L; and / or, the molar concentration of the sodium bicarbonate aqueous solution is 1.0-3.0 mol / L.

8. The method for preparing methanol according to claim 1, characterized in that: The dropping in steps 1) and 2) is performed at 70-80° C.; and / or, the dropping in steps 1) and 2) is performed at a pH of 9.5-10.5; and / or, in step 3), the pH value of the system is adjusted to 9.5-10.

5.

9. The method for preparing methanol according to claim 1, characterized in that: The high-pressure blasting in step 4) is performed by a high-pressure blasting nozzle; and / or, in step 5), the dropping of tetrabutyl silicate is carried out at 70-80°C for 6-8 hours; and / or, the tetrabutyl silicate accounts for 100-150ppm of the mass of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst; and / or, in step 6), the heating and setting temperature is 320-350°C.

10. The method for preparing methanol according to claim 1, characterized in that: The water-soluble copper salt is selected from one or both of copper sulfate and copper chloride; and / or the tetraalkyl zirconium is tetraethyl zirconium; and / or the tetraalkyl titanate is tetraisopropyl titanate.

11. The method for preparing methanol according to claim 1, characterized in that: In step 1), the titration is performed at a pH of 9-11; and / or, in step 2), the heating treatment is performed at a temperature of 50-600° C. for 16-24 hours.

12. The method for preparing methanol according to claim 1, characterized in that: The first-stage fixed bed reactor comprises an inner chamber and an outer chamber; the inner chamber comprises multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a tower type, and multiple groups of homogenizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the homogenizing plates of the inner chamber and the outer chamber; and a filter is arranged at the bottom of the outer chamber.

13. The method for preparing methanol according to claim 12, characterized in that: The effective volumes of the inner chamber and the outer chamber are the same; and / or the residence time of the reaction gas in the inner chamber and the outer chamber is the same.

14. The method for preparing methanol according to claim 1, characterized in that: The residence time of the raw gas in the first-stage fixed bed reactor is 135-160s; and / or, after the hydrogenation reaction in the first-stage fixed bed reactor is completed, the conversion rate of carbon dioxide is 38.0%-50%; and / or, the volume of the first-stage fixed bed reactor is 135-150m 3 The volume of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 75-90m 3 .

15. The method for preparing methanol according to claim 1, characterized in that: The second-stage fixed bed reactor adopts a multi-layer tray reflux design, and phase separation is completed simultaneously during the reaction process. The bottom is a high-pressure methanol gas-liquid phase mixed product, and the top is an unreacted mixed gas phase.

16. The method for preparing methanol according to claim 1, characterized in that: The volume of the second stage fixed bed reactor is 50-58m 3 ; and / or, the volume of the first-stage fixed bed reactor is 2.5-3.0 times the volume of the second-stage fixed bed reactor; and / or, the residence time of the reaction system in the second-stage fixed bed reactor is 35-45s.

17. The method for preparing methanol according to claim 1, characterized in that: In the second-stage fixed-bed reactor, the effective self-circulation ratio of the reaction system is 3.5-6.0; and / or, after the hydrogenation reaction in the second-stage fixed-bed reactor is completed, the cumulative conversion rate of carbon dioxide is 80.4%-91.5%.

18. The method for preparing methanol according to claim 1, characterized in that: The third-stage fixed bed reactor comprises an inner chamber and an outer chamber; the inner chamber comprises multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a tower type, and multiple groups of homogenizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the homogenizing plates of the inner chamber and the outer chamber; and a filter is arranged at the bottom of the outer chamber.

19. The method for preparing methanol according to claim 1, characterized in that: The volume of the third stage fixed bed reactor is 15-20m 3 ; and / or, the volume of the second-stage fixed bed reactor is 2.0-4.0 times the volume of the third-stage fixed bed reactor; and / or, the residence time of the reaction system in the third-stage fixed bed reactor is 60-90s; and / or, after the hydrogenation reaction in the third-stage fixed bed reactor is completed, the cumulative conversion rate of carbon dioxide is 87.5%-95.0%.

20. The method for preparing methanol according to claim 1, characterized in that: The temperature of the first-stage fixed bed reactor is 150-350°C and the pressure is 5.0-20.0MPa; and / or, the temperature of the second-stage fixed bed reactor is 120-240°C and the pressure is 15.0-20.0MPa; and / or, the temperature of the third-stage fixed bed reactor is 150-350°C and the pressure is 5.0-20.0MPa.

21. The method for preparing methanol according to claim 1, characterized in that: The carbon dioxide is derived from a by-product of petroleum refining processes.

22. The method for preparing methanol according to claim 21, characterized in that: The volume content of carbon dioxide in the by-products of the petroleum refining process is 80%-90%.

23. The method for preparing methanol according to claim 21, characterized in that: The method also includes the steps of filtering, washing with water, washing with ammonia water, removing suspended solids, and treating with a pressure swing adsorption (PSA) device for the byproducts of the petroleum refining process. After these steps, the volume content of carbon dioxide is 98.0%-99.5%.

24. The method for preparing methanol according to claim 1, characterized in that: After the carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor from the bottom for hydrogenation reaction. The gas flow after the reaction flows out from the bottom of the first-stage fixed bed reactor, enters the condenser for condensation, and enters the first methanol phase separation device for phase separation after decompression.

25. The method for preparing methanol according to claim 24, characterized in that: The molar ratio of carbon dioxide to hydrogen is 1:3-4.

5.

26. The method for preparing methanol according to claim 24, characterized in that: The gas flow at the top of the first methanol phase separation device and the added hydrogen are mixed and pressurized, and then enter the second-stage fixed bed reactor from the lower middle part. The mixed gas flow undergoes a hydrogenation reaction in the second-stage fixed bed reactor, and the liquid component after the reaction flows out from the bottom of the second-stage fixed bed reactor and enters the first methanol phase separation device for phase separation.

27. The method for preparing methanol according to claim 26, characterized in that: The amount of the added hydrogen accounts for 4%-8% of the amount of hydrogen entering the first-stage fixed bed reactor.

28. The method for preparing methanol according to claim 26, characterized in that: The incompletely reacted gas is discharged from the top of the second-stage fixed bed reactor, mixed with the second added hydrogen and pressurized, and then enters the third-stage fixed bed reactor for hydrogenation reaction. The mixed gas after the reaction flows out from the bottom of the third-stage fixed bed reactor and enters the second methanol phase separation device for phase separation.

29. The method for preparing methanol according to claim 28, characterized in that: The amount of the second added hydrogen accounts for 0.3% to 0.6% of the amount of hydrogen entering the first stage fixed bed reactor.

30. The method for preparing methanol according to claim 28, characterized in that: The tail gas at the top of the third-stage fixed bed reactor is introduced into a pressure swing adsorption (PSA) device after decompression treatment to adsorb hydrogen, and then desorb and recover the hydrogen.

31. The method for preparing methanol according to claim 30, characterized in that: The recovered hydrogen is used as the source of the supplementary hydrogen entering the second-stage fixed bed reactor and the second supplementary hydrogen entering the third-stage fixed bed reactor.

32. The method for preparing methanol according to claim 28, characterized in that: The liquid crude methanol separated by the first methanol phase separation device and the second methanol phase separation device is subjected to two-stage distillation separation, and the pressure of the second stage distillation is higher than the pressure of the first stage distillation.

33. A method for preparing ethylene glycol, comprising the steps of preparing ethylene from methanol via MTO technology, preparing ethylene oxide from ethylene oxidation, and preparing ethylene glycol from ethylene oxide hydrolysis; characterized in that: The preparation method further comprises the step of preparing methanol by using the method for preparing methanol according to any one of claims 1 to 32.

34. A method for preparing polyethylene terephthalate, comprising the steps of sequentially subjecting terephthalic acid and ethylene glycol to a first esterification, a second esterification, a first prepolymerization, a second prepolymerization and a final polymerization; characterized in that: The preparation method also includes the step of preparing ethylene glycol by the preparation method of ethylene glycol described in claim 33; the preparation method also includes the step of adding an esterification catalyst and a composite stabilizer to terephthalic acid and ethylene glycol before performing the first esterification step; the esterification catalyst is selected from a combination of one or more of zinc acetate, manganese acetate, potassium acetate, sodium acetate, cobalt acetate, calcium acetate and lithium acetate; the composite stabilizer includes an amine stabilizer, sodium bisulfite and a phosphorus stabilizer.

35. The method for preparing polyethylene terephthalate according to claim 34, characterized in that: The esterification catalyst is a mixture of zinc acetate, manganese acetate and lithium acetate; and / or, the mass of the esterification catalyst accounts for 100-200 ppm of the mass of the polyethylene terephthalate; and / or, the amine stabilizer is selected from a combination of one or more of triethanolamine, triethylamine, tert-butylamine and diisopropylamine; and / or, the phosphorus stabilizer is selected from a combination of one or more of triphenyl phosphite, triethyl phosphate, trimethyl phosphate and phosphoric acid.

36. The method for preparing polyethylene terephthalate according to claim 35, characterized in that: In the mixture, the molar ratio of zinc acetate, manganese acetate and lithium acetate is 1:0.3-0.6:0.5-0.

75.

37. The method for preparing polyethylene terephthalate according to claim 34, characterized in that: The mass of the amine stabilizer accounts for 35-50 ppm of the mass of the polyethylene terephthalate; and / or, the mass of the sodium bisulfite accounts for 15-20 ppm of the mass of the polyethylene terephthalate; and / or, the mass of the phosphorus stabilizer accounts for 125-150 ppm of the mass of the polyethylene terephthalate.

38. The method for preparing polyethylene terephthalate according to claim 34, characterized in that: The preparation method also includes the step of adding a liquid phase tracer into terephthalic acid and ethylene glycol before the first esterification step; the liquid phase tracer is selected from a combination of one or more of isophthalic acid, phthalic acid, trimellitic acid, pyromellitic acid, cyclohexanedicarboxylic acid, 2,2,4,4-tetramethylcyclobutanedicarboxylic acid, pentaerythritol, neopentyl glycol, 1,2-dibutanol, 2,2,4,4-tetramethylcyclobutane dimethanol and 1,4-cyclohexanedimethanol; and / or, the preparation method also includes the step of adding a solid phase tracer in the second esterification step; the solid phase tracer is selected from a combination of one or more of hydrophilic nano-silica, γ-nano-aluminum oxide, nano-barium sulfate powder, sub-nano composite calcium carbonate-magnesium carbonate, sub-nano-attapulgite powder and multi-element light metal zeolite nano-powder.

Citation Information

Patent Citations

  • Nanometer supported solid-phase titanium-based multi-metal catalyst as well as preparation method and application thereof

    CN117567730A

  • Steam Reforming Of Methanol

    US20140308597A1

  • Catalysts and methods for methanol synthesis from direct hydrogenation of syngas and / or carbon dioxide

    US20190076828A1

  • Catalyst for methanol synthesis

    JP1998216522A